Classification of agarwood types (malaccensis and crassna) between oil and smoke using E-nose with CBR classifier - Mujahid, Mohamad; Muhammad Sharfi, Najib; Suhaimi, Mohd Daud; Nurdiyana, Zahed; Muhamad Faruqi, Zahari; Nur Farina, Hamidon Majid; Suziyanti, Zaib; Hadi, Manap (Springer, 2020)
The issue of quality of agarwood quality among sellers and buyers is still ongoing due to manual olfactory methods. This study purpose classification of Malaccensis and Crassna agarwood in oil and smoke by electronic nose using Case-based Reasoning classifier. The CBR performance measurement shows that classification of agarwood Malaccensis and Crassna for both oil and smoke using CBR technique can achieve 100% classification success.